Mulheres em vivência de rua e a integralidade no cuidado em saúde - Santos, Verônica Bem dos (2014)
The present dissertation refers to a theoretical and empirical study, of qualitative nature, which addresses the health of women with street living experiences. Elaborated under the academic article format, it aims, in each one of them, respectively: to discuss and to problematize the usage of the term street situation used to refer to a variety of people who inhabit the streets, institutions or irregular dwellings; to reflect on the researcher-researched universe relation on an ethnographic study with difficult access populations; and to discuss around the transversalities of this group of women‟s health care. The theoretical data were collected through a detailed research on the webpage of the Ministry of Social Development and Hunger Combat (MSD), whence three public documents that compose the attention policy to people in street situation were chosen to compose the analysis: PNAS/2004; Decree nº 7.053/2009; National Typification for the Social Assistance Services. The empirical data were produced through ethnographic method, using participant observation and field journal record. The data interpretation is conducted based on Critical Social Psychology, supported by the Social Representations Theory, Gender Studies and interdisciplinary studies about the street living experience and health. The results, presented in three academic articles titled: ‟To look through seeing eyes‟: Reflections about the street situation‟ term , Difficult access population and the psychologist researcher implication: an ethnographic study with women who live on the streets , and Health care of women living on the streets and health integrality . We conclude that a thorough care to people in street situation demands a view that encompasses its various problems, needs and desires, which includes rethinking the commonly used nomenclatures. Furthermore, in methodological terms, we emphasize that the ethnographic method meets Critic Social Psychology, demanding a sensitive view implicated in the research process. Finally, we highlight that women with street living experience represent a very diverse population in its characteristics and complex in its needs, requiring a care that takes into account its transversalities, especially those which refer to interactions and relations established within its boundaries.